2024
DOI: 10.1002/acp.4184
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cancer misinformation: Predictors of false belief and false memory formation

Nora King,
Ciara M. Greene

Abstract: Previous research has shown that people sometimes come to believe in misinformation presented in the form of fake news, and even form false memories for the fabricated events described. This study aimed to investigate the effects of analytical reasoning, attitudes to complementary and alternative medicine, bullshit receptivity, and previous experience with cancer on the formation of false memory and false belief for cancer related misinformation. Participants (N = 466) were exposed to four fake news stories an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The idea that pseudoscience endorsement might be associated in some way with susceptibility to memory distortions has already been tested in previous studies. For instance, in line with results observed regarding the association between political views and false memory promotion (Greene et al, 2021 ; Murphy et al, 2021 ), beliefs about vaccination have been shown to influence the generation of false memories for fabricated fake news related with the COVID-19 pandemic, with individuals falsely remembering more fake news congruent with their prior beliefs (Greene et al, 2022 ; though see King & Greene, 2024 for a lack of association between previous pseudoscientific beliefs and false memories for cancer-related fake news). From a different point of view, Chow et al ( 2021 ) observed that erroneous health beliefs connecting different pseudotherapies and health conditions were frequently associated with the perception of nonzero contingency between those events experienced in one’s daily life.…”
Section: Introductionsupporting
confidence: 57%
“…The idea that pseudoscience endorsement might be associated in some way with susceptibility to memory distortions has already been tested in previous studies. For instance, in line with results observed regarding the association between political views and false memory promotion (Greene et al, 2021 ; Murphy et al, 2021 ), beliefs about vaccination have been shown to influence the generation of false memories for fabricated fake news related with the COVID-19 pandemic, with individuals falsely remembering more fake news congruent with their prior beliefs (Greene et al, 2022 ; though see King & Greene, 2024 for a lack of association between previous pseudoscientific beliefs and false memories for cancer-related fake news). From a different point of view, Chow et al ( 2021 ) observed that erroneous health beliefs connecting different pseudotherapies and health conditions were frequently associated with the perception of nonzero contingency between those events experienced in one’s daily life.…”
Section: Introductionsupporting
confidence: 57%